Penggunaan Konseling Kelompok Melalui Teknik Reinforcement Positif Untuk Mengurangi Prokrastinasi Akademik Pada Mahasiswa Orda Jawa Barat - Jamaluddin, Muhammad; Kafrawi, Fahmi; Hidayat, Gumelar Sastra (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Procrastination behavior is often found in various patterns of human life, such as in this research which discusses procrastination among students. Procrastination itself arises due to several factors. The aim of this research is to find out how the influence of group counseling can reduce academic procrastination behavior with students as the subject. This research took subjects from students who were in the West Java Regional Student Organization in Malang. The sample taken was 15 people who were given group counseling treatment through positive reinforcement techniques, using quantitative methods, namely Quasi Experimental. After looking at the results, it was found that there were around 66.7% of the total population who had high academic procrastination before treatment, then after being given treatment it fell to 0.0% then 20% had the medium category and 80% had the low category. . It can be concluded from this research that there is a good influence in reducing academic procrastination in students by using group counseling through positive reinforcement techniques.